## Trending News

Promoted

# MATH HELP ! SOLVING WITH ELIMINATION ! NON- STANDARD FORM?

6x - 6y + 8 = 14

8y = 4x + 4

### 3 Answers

Relevance

- M3Lv 78 years agoFavorite Answer
first convert it to standard form

6x - 6y = 6

or x - y = 1 ......(i)

4x -8y = -4

or x - 2y = -1 .....(ii)

(i) - (ii)

y = 2

substitute in (i)

x = 3

ans: (3,2)

-----

- gAytheistLv 68 years ago
The first thing to do is to get the equations into standard form:

6x -6y = 6

-4x + 8y = 4

divide out the 6 from the first equation and divide the second equation by 4. You will then have:

x - y = 1

-x + 2y = 1

Add the two equations. the x's cancel out and you have:

2y - y = 2

y = 2

substitute y=2 into the first equation to get

x - 2 = 1

x = 3

- KateLv 48 years ago
6x - 6y = 6 (1)

4x - 8y = -4 (2)

(1) x 4:

24x - 24y = 24 (3)

(2) x 6:

24x - 48y = -24 (4)

(3) - (4):

24y = 48

y = 2

Substitute y = 2 into (1):

6x - 12 = 6

6x = 18

x = 3

Therefore x = 3 and y = 2.

Still have questions? Get your answers by asking now.